Viability Analysis of Spore-Based Biosensors in Sterilization Processes - Julio Arreola; Jan Oberländer; Michael Keusgen; Michael J. Schöning (Proceedings, 2017)
The use of microbiological tests is the state-of-the-art method to validate the efficacy of several sterilization processes, for instance, gaseous H2O2 from aseptic filling machines. [...]